PENERAPAN PENDEKATAN PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PEMBELAJARAN MATEMATIKA DAN MOTIVASI BELAJAR SISWA MTs PADA MATERI ALJABAR - Mutia Yuniar; Citra Megiana Pertiwi (IKIP Siliwangi, 2022)
This research is Classroom Action Research which aims to improve mathematics learning and students' motivation to learn mathematics in one of the MTs in Cimahi City by using a problem-based learning approach to class IX students. This research consisted of three cycles with 10 students as the subject. The research instrument used consisted of an affective assessment instrument and a cognitive test using a learning motivation attitude scale and teaching materials in the form of LKPD categorized as successful to increase student learning motivation, which was above 80%. For the mathematics learning outcomes of students in cycle 1, it shows 40% or an average value of 64, for cycle 2 it shows 60% or an average value of 71, for cycle 3 it shows 80% or an average value of 84. Meanwhile, for cycle 1, students' learning motivation shows 74 %, in the second cycle the student's learning motivation showed 78.4%, and the third cycle of the student's learning motivation showed 81.4%. So that each cycle for mathematics learning outcomes and students' learning motivation using a problem-based learning approach increases even though there are still some obstacles during the learning process.